The impact of investment diversification on financial performance of commercial banks in Ethiopia - Aregu Asmare Hailu; Abel Worku Tassew (Financial Studies, 2018)
Commercial banks play an important role in the development of a country. A sound, progressive and dynamic banking system is a fundamental requirement for economic development. Thus, the purpose of this study was investigating the impact of investment diversification on financial performance of 17 Ethiopian Commercial Banks covering the period of 2013-2017.Quantitative research approach was used and the data was analysed by using panel random effect regression model. The finding of the study shows that investment in financial assets, government security, insurance, loan portfolio and investment size have positive significant impact on financial performance of Banks in Ethiopia. Whereas, interest and exchange rate volatility have negative significant impact on financial performance of commercial Banks in Ethiopia. The study concludes that investment diversification positively affects the financial performance of commercial banks in Ethiopia. Therefore, banks should focus its work to promote the confidence in portfolio diversification, develop marketing policies that encourage its use and establish the best combination of assets that can yield an efficient portfolio.
Keywords: F63; G11; G32; 330; economic development; efficient portfolio; risk management